2019
DOI: 10.1161/strokeaha.118.024241
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Participatory Research

Abstract: Clinical researchers strive to improve outcomes for the subjects of their research. Whether testing a novel drug, procedure, or behavioral intervention, the goal is to positively impact the recipient's health. It is the academic researcher, therefore, who identifies the health need and then devises a strategy to address that need. Contrast this to research in which the subject is not only the beneficiary of the product of the research but is a co-creator of the research from its inception to completion. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 7 publications
1
33
0
1
Order By: Relevance
“…Second, we need to clarify the concept of audience orientation when designing social marketing solutions. While community-based participatory approaches are utilized to effect social change (Springer & Skolarus, 2019), we need a much more consistent adoption of this approach, especially when attempting behavior change with social marketing tools. A good use of audience orientation would be to approach the community with the social problem, involve them as peers in the social change team, have them tell us what the problem is, and then co-design solutions and behavior change strategies.…”
Section: Recommendationsmentioning
confidence: 99%
“…Second, we need to clarify the concept of audience orientation when designing social marketing solutions. While community-based participatory approaches are utilized to effect social change (Springer & Skolarus, 2019), we need a much more consistent adoption of this approach, especially when attempting behavior change with social marketing tools. A good use of audience orientation would be to approach the community with the social problem, involve them as peers in the social change team, have them tell us what the problem is, and then co-design solutions and behavior change strategies.…”
Section: Recommendationsmentioning
confidence: 99%
“…8 This approach to research addresses gaps in academic knowledge that are identified as priorities and most relevant to the patients, who are in fact most knowledgeable about the circumstances that affect their own health. 8,16 Employment consequences…”
Section: Discussionmentioning
confidence: 99%
“…Also noteworthy are the challenges experienced involving the necessity of virtual communication among community partners during the COVID-19 pandemic. Open communication and routine interaction among partners have been identified as a strategy to facilitate transparency of project logistics and expectations [ 24 , 25 ]. Consequently, the reduced face-to-face contact in the community impacted the intimacy that meaningful partnership-building and sustainability requires.…”
Section: Discussionmentioning
confidence: 99%